Extent of Response of Corn Growth Traits to Potassium and Humic - Saad Ali Hussein Al-Akabi; Tahseen Ali Ibrahim AL-Abtan; Amjad Shaker Hamoud Al-Bawi; Enas Saad Sobeih (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Maize (Zea mays L.) is one of the world’s most important cereal crops, serving as a key food, feed, and industrial raw material. In Iraq, maize productivity remains below the global average due to nutrient imbalances and suboptimal fertilization practices. Specific Background: Potassium plays a crucial physiological role in plant growth, yet its availability is limited in many Iraqi soils. Additionally, humic acid, when applied as a foliar spray, enhances nutrient absorption and photosynthetic efficiency. Knowledge Gap: Limited studies have explored the interactive effects of potassium fertilization and foliar-applied humic acid on maize vegetative growth under Iraqi soil conditions. Aims: This study aimed to evaluate the response of maize (cv. 5018) vegetative traits to different levels of potassium (120 and 140 kg ha⁻¹) and humic acid (3 and 4 ml L⁻¹) applied through foliar feeding. Results: The results showed that 120 kg ha⁻¹ potassium significantly enhanced plant height (249.50 cm), stem diameter (2.38 cm), number of leaves (15.64 plant⁻¹), and dry weight (182.94 g). Foliar application of humic acid at 4 ml L⁻¹ further improved stem diameter and leaf number. Novelty: This research highlights the synergistic potential of potassium and humic acid in optimizing maize vegetative performance in potassium-limited soils. Implications: The findings provide a practical basis for refining fertilization strategies to enhance maize productivity in similar agroecological regions.Highlight : Potassium levels of 120 and 140 kg ha⁻¹ increased plant height and stem diameter. Humic acid at 3 and 4 ml L⁻¹ improved stem diameter and number of leaves. Combined potassium and humic treatments enhanced overall vegetative growth. Keywords : Maize, Potassium, Foliar Feeding, Humic Acid, Growth Traits